Laminated substrate film for vapor deposition and vapor deposition laminated film
By using a combination of methacrylic copolymer and thermoplastic resin in the laminated base film for evaporation, the problem of poor adhesion between the methacrylic resin layer and the vapor deposition layer is solved, and high heat resistance and adhesion are achieved, which is suitable for a variety of decoration and electronic equipment applications.
Patent Information
- Application Number
- CN202380054146.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-21
- Filing Date
- 2023-07-21
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, the methacrylic resin layer has poor adhesion to the vapor deposition layer, which makes it difficult to use in certain uses.
The laminated base film for evaporation is adopted, which consists of a methacrylic copolymer and a thermoplastic resin, and the adhesion with the evaporation layer is improved by coextruding body and anchoring layer.
It achieves high heat resistance, flexibility and dimensional stability, improves adhesion to the vapor deposition layer, and is suitable for a variety of purposes, including interior and exterior decoration of automobiles and interior and exterior decoration of electronic equipment.
Smart Images

Figure CN119731027A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a vapor deposition laminated base film and a metallic sheet, etc. More specifically, the present invention relates to a vapor deposition laminated base film having high heat resistance, low water absorption, high mechanical strength, and high wetting tension, for providing a vapor deposition layer on a layer formed of a methacrylic copolymer, and a vapor deposition laminated film having the vapor deposition laminated base film and the vapor deposition layer and having excellent adhesion to the vapor deposition layer. Background Art
[0002] Methacrylic resins are excellent in transparency, scratch resistance, weather resistance, etc. Laminated films using methacrylic resins as surface materials are used in applications that require high appearance, surface strength, durability, etc. for house walls, furniture, home appliances, electronic devices, display devices, etc. In such applications, laminated films further provided with a metal vapor-deposited layer are required to impart functions such as designability, scratch resistance, antistatic properties, conductivity, and gas barrier properties.
[0003] However, in general, when a deposited layer is provided on a laminated film using a methacrylic resin layer as the surface material, the adhesion between the methacrylic resin layer and the deposited layer is very poor, and thus it is difficult to use. In order to improve the adhesion between the methacrylic resin layer and the deposited layer, an organic anchor layer is sometimes formed in advance, but due to the difference in material properties between the methacrylic resin layer and the anchor layer, the methacrylic resin and the anchor layer may be peeled off.
[0004] In order to improve the adhesion with the vapor-deposited layer, Patent Document 1 proposes an acrylic resin laminate, wherein the substrate uses a heat-resistant acrylic resin obtained by copolymerizing methyl methacrylate units, maleic anhydride units, and aromatic vinyl compound units. The adhesion is improved by copolymerization of maleic anhydride units, but the obtained laminate is brittle. Patent Document 2 proposes a laminated film for direct metal vapor deposition, which is formed by laminating a styrene resin layer (B1) formed by a resin composition (b1) containing a copolymer of a styrene monomer and alkenyl cyanide on at least one surface of a thermoplastic resin layer (A) formed by a resin composition (a) containing a methacrylic resin. The adhesion is improved by copolymerization of alkenyl cyanide, but the heat resistance is insufficient. In addition, Patent Document 3 proposes a substrate film, which is formed by forming a glutarimide acrylic resin having a glutarimide structural unit and a methyl methacrylate structural unit to obtain a film and biaxially stretching it. By including a glutarimide structural unit, the adhesion is improved, but the water absorption is high and the dimensional stability is poor.
[0005] As described above, there is still room for research on methods for improving adhesion with a vapor-deposited layer and balancing heat resistance, flexibility, and dimensional stability at a high level.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2008-94064
[0009] Patent Document 2: Japanese Patent Application Publication No. 2011-143584
[0010] Patent Document 3: Japanese Patent Application Laid-Open No. 6-256537 Summary of the invention
[0011] Problems to be solved by the invention
[0012] In view of the above circumstances, an object of the present invention is to provide a laminated base film having high heat resistance, flexibility and dimensional stability and having a vapor-deposited layer provided on at least one surface thereof, and a vapor-deposited laminated film comprising the laminated base film and the vapor-deposited layer.
[0013] Methods used to solve problems
[0014] The present inventors have conducted intensive studies to achieve the above-mentioned object, and as a result, have completed the present invention including the following aspects. [1]
[0016] A laminated substrate film for vapor deposition, comprising a layer formed of a methacrylic resin composition (I) containing a methacrylic copolymer (a) having a glass transition temperature of 135° C. or higher, and a layer formed of a resin composition (T) containing a thermoplastic resin (b), wherein the methacrylic copolymer (a) has 5 to 73% by mass of methyl methacrylate units, 25 to 70% by mass of a structural unit (r) represented by the following formula (1), 1 to 48% by mass of an α-methylstyrene unit, 1 to 48% by mass of at least one selected from the group consisting of a styrene unit and a maleic anhydride unit, and 0 to 20% by mass of an unsubstituted or N-substituted maleimide unit.
[0017]
[0018] (In formula (I), R 1 are each independently a hydrogen atom or a methyl group, R 2 It is a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an organic group having 6 to 15 carbon atoms including an aromatic ring. [2]
[0020] The laminated base film for vapor deposition according to [1], wherein the glass transition temperature of the methacrylic resin composition (I) is 145° C. or higher. [3]
[0022] The laminated base film for vapor deposition according to [1], wherein the methacrylic resin composition (I) has a saturated water absorption of 3.0% by mass or less. [4]
[0024] The laminated base film for vapor deposition according to [1], wherein the thermoplastic resin (b) is a polycarbonate resin. [5]
[0026] The laminated substrate film for vapor deposition according to [1], wherein the layer formed from the methacrylic resin composition (I) and the layer formed from the resin composition (T) are co-extruded molded products. [6]
[0028] The laminated base film for vapor deposition according to [1], wherein an anchor layer is laminated on the layer formed from the methacrylic resin composition (I). [7]
[0030] A vapor-deposited laminated film, characterized in that, in the vapor-deposited laminated base film described in [1], a layer formed by a methacrylic resin composition (I) is laminated on one surface of a layer formed by a resin composition (T), and a vapor-deposited layer is provided on the surface on the side of the layer formed by the methacrylic resin composition (I). [8]
[0032] A vapor-deposited laminated film, characterized in that, in the vapor-deposited laminated base film described in [1], a layer formed of a methacrylic resin composition (I) is laminated on both sides of a layer formed of a resin composition (T), and a vapor-deposited layer is provided on any one side. [9]
[0034] A metallic sheet characterized by being formed by laminating a thermoplastic resin sheet on the vapor-deposited layer side of the vapor-deposited laminate film described in [7] or [8].
[10]
[0036] The metallic sheet according to [9], wherein the vapor-deposited layer and the thermoplastic resin sheet are laminated with an adhesive layer interposed therebetween.
[11]
[0038] The metallic sheet according to [9], wherein the vapor-deposited layer and the thermoplastic resin sheet are laminated by dry lamination.
[12]
[0040] A metallic molded product, characterized in that the vapor-deposited layer side of the vapor-deposited laminated film described in [7] or [8] is bonded to a molded product.
[13]
[0042] A metallic molded product, characterized in that the surface of the metallic sheet described in [9] on which the thermoplastic resin sheet is laminated is bonded to a molded product.
[14]
[0044] A metallic molded product, characterized in that the surface of the metallic sheet described in
[10] on which the thermoplastic resin sheet is laminated is bonded to a molded product.
[15]
[0046] A metallic molded product, characterized in that the surface of the metallic sheet described in
[11] on which the thermoplastic resin sheet is laminated is bonded to a molded product.
[0047] Effects of the Invention
[0048] The laminated substrate film for vapor deposition of the present invention has high heat resistance, flexibility and dimensional stability and can be suitably used in a vapor deposition process.
[0049] The laminated substrate film for vapor deposition of the present invention has high adhesion to the vapor deposition layer and can provide high-performance functions in various applications. The metallic sheet and metallic molded product, which are one embodiment of the laminated substrate film for vapor deposition of the present invention, have excellent metallic appearance and are therefore useful as interior and exterior decorative materials for vehicles, interior and exterior decorative materials for electronic devices, adhesives for building materials, plastic window frames and other construction and building materials fields, housings for home appliances, and the like. DETAILED DESCRIPTION
[0050] In this specification, unless otherwise explicitly stated in the specification or clearly contradicted by the context, the singular forms (a, an, the, etc.) include both the singular and the plural.
[0051] The laminated substrate film for vapor deposition of the present invention is a film for vapor deposition. Vapor deposition includes physical vapor deposition and chemical vapor deposition. The laminated substrate film for vapor deposition of the present invention can be appropriately prepared by physical vapor deposition methods such as vacuum vapor deposition, sputtering, ion plating, or chemical vapor deposition, etc., which are known in the art. Among them, vacuum vapor deposition is used as a preferred method.
[0052] The methacrylic resin composition (I) used in the laminated substrate film for vapor deposition of the present invention contains a methacrylic copolymer (a). In a preferred embodiment, the methacrylic resin composition (I) contains a methacrylic copolymer (a) and a methacrylic resin. The content of the methacrylic copolymer (a) in the methacrylic resin composition (I) is preferably 51% by mass or more, more preferably 65% by mass or more, further preferably 80% by mass or more, and particularly preferably 90% by mass or more, and the methacrylic copolymer (a) may be the only component.
[0053] [Methacrylic acid copolymer (a)]
[0054] The methacrylic copolymer (a) of the present invention contains 5 to 73% by mass of methyl methacrylate units, 25 to 70% by mass of structural units (r), 1 to 48% by mass of α-methylstyrene units, 1 to 48% by mass of at least one selected from the group consisting of styrene units and maleic anhydride units, and 0 to 20% by mass of unsubstituted or N-substituted maleimide units. As described above, the methacrylic copolymer (a) also includes a methacrylic copolymer (a) in which the unsubstituted or N-substituted maleimide units are 0% by mass, that is, the methacrylic copolymer (a) does not contain unsubstituted or N-substituted maleimide units. The methacrylic copolymer (a) used in the present invention may also contain other vinyl monomer units that can be copolymerized with methyl methacrylate. In the present invention, the structural unit in the polymer refers to a repeating unit constituting the polymer or a unit formed by derivatizing at least a part of the repeating unit (for example, an unsubstituted or N-substituted glutarimide unit). In addition, in this specification, the methyl methacrylate unit, the structural unit (r), the α-methylstyrene unit, the styrene unit, and other vinyl monomer units are sometimes collectively referred to as the term "structural unit".
[0055] In the methacrylic copolymer (a) of the present invention, the ratio of the methyl methacrylate unit is 5 to 73% by mass, preferably 6 to 70% by mass, more preferably 6 to 60% by mass, and further preferably 6 to 50% by mass relative to the total structural units. From the viewpoint of transparency and thermal decomposition resistance of the obtained methacrylic copolymer, the ratio of the methyl methacrylate unit is preferably within the above range.
[0056] In the methacrylic copolymer (a) of the present invention, the ratio of the α-methylstyrene unit is 1 to 48% by mass, preferably 3 to 40% by mass, more preferably 5 to 35% by mass, and still more preferably 7 to 30% by mass relative to the total structural units. The ratio of the α-methylstyrene unit is preferably within the above range from the viewpoints of heat resistance, rigidity, and thermal decomposition resistance of the obtained methacrylic copolymer, productivity (polymerizability), inhibition of hindrance of the glutarimidization reaction caused by intramolecular cyclization of two adjacent structural units derived from (meth)acrylic acid described later, and dimensional stability of the laminated base film.
[0057] In the methacrylic copolymer (a) of the present invention, the ratio of styrene units or maleic anhydride units is 1 to 48% by mass relative to all structural units, preferably 3 to 40% by mass, more preferably 5 to 35% by mass, and further preferably 7 to 30% by mass. From the viewpoints of the heat decomposition resistance, fluidity, and heat resistance of the obtained methacrylic copolymer, and the viewpoints of inhibiting the glutarimidization reaction caused by the intramolecular cyclization of two adjacent structural units derived from (meth) acrylic acid described later, and the viewpoints of the appearance of the laminated substrate film, etc., it is preferred that the ratio of styrene units is within the above range. From the viewpoints of the heat decomposition resistance, fluidity, and the viewpoints of inhibiting the glutarimidization reaction caused by the intramolecular cyclization of two adjacent structural units derived from (meth) acrylic acid described later, and the viewpoints of the appearance of the laminated substrate film, etc., it is preferred that the ratio of maleic anhydride units is within the above range. In the present invention, it is preferred to include styrene units with better productivity.
[0058] In the methacrylic copolymer (a) of the present invention, the total ratio of α-methylstyrene units and styrene units is preferably 2 to 40% by mass, more preferably 5 to 35% by mass, and further preferably 10 to 30% by mass relative to all structural units. When the total ratio of α-methylstyrene units and styrene units is within the above range, it is not easy to hinder the glutarimidization reaction caused by the intramolecular cyclization of two adjacent structural units derived from (meth) acrylic acid described later. In addition, relative to the total ratio of α-methylstyrene units and styrene units, the ratio of α-methylstyrene units is preferably 30 to 95% by mass, more preferably 35 to 90% by mass, and further preferably 40 to 85% by mass. When the ratio of α-methylstyrene units is within the above range, the methacrylic copolymer used in the present invention has an excellent balance between heat resistance and low water absorption, so the dimensional stability of the obtained film is good.
[0059] The structural unit (r) is a structural unit having a ring structure selected from the group consisting of N-substituted or unsubstituted glutarimide units in the main chain.
[0060] The N-substituted or unsubstituted glutarimide unit is a unit having an N-substituted or unsubstituted 2,6-dioxopiperidinediyl structure. Examples of the unit having an N-substituted or unsubstituted 2,6-dioxopiperidinediyl structure include a structural unit represented by formula (I).
[0061]
[0062] In formula (I), R 1 Each independently represents a hydrogen atom or a methyl group, preferably 2 R 1 All are methyl. 2 It is a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an organic group having 6 to 15 carbon atoms containing an aromatic ring, preferably a methyl group, an n-butyl group, a cyclohexyl group, or a benzyl group, more preferably a methyl group, an n-butyl group, or a cyclohexyl group, and most preferably a methyl group.
[0063] In addition, the structural unit (r) can be formed, for example, by adding an imidizing agent to a precursor polymer in an extruder, kneading, and reacting the imide cyclization reaction. In a preferred embodiment, the structural unit represented by formula (I) can be formed, for example, by reacting the corresponding acid anhydride (IIa) with R 2 It can be generated by the reaction of an imidizing agent represented by NH2, or by an intramolecular cyclization reaction of a copolymer having a partial structure of formula (III). In order to convert the structural unit represented by formula (III) into the structural unit represented by formula (I) by the intramolecular cyclization reaction, it is preferably heated.
[0064] Solution (i)
[0065]
[0066] (Where R 1 , R 2 As defined above.)
[0067] The N-substituted or unsubstituted glutarimide unit can be obtained by the method described in WO2005 / 10838A1, Japanese Patent Application Laid-Open No. 2010-254742, Japanese Patent Application Laid-Open No. 2008-273140, Japanese Patent Application Laid-Open No. 2008-274187, etc., specifically, by reacting an imidizing agent such as ammonia, methylamine, ethylamine, diethylamine, n-propylamine, isopropylamine, n-butylamine, isobutylamine, tert-butylamine, n-hexylamine, etc., an amine containing an aliphatic hydrocarbon group such as aniline, toluidine, trichloroaniline, N-methylbenzylamine, etc., an amine containing an aromatic hydrocarbon group such as cyclohexylamine, N-methylcyclohexylamine, etc., an amine containing an alicyclic hydrocarbon group such as urea, 1,3-dimethylurea, 1,3-diethylurea, 1,3-dipropylurea, with two adjacent structural units derived from methyl methacrylate or glutaric anhydride units. Among them, primary amine is essential, and secondary amine can also be used in combination. As the primary amine, methylamine is preferred. During the imidization reaction, a part of the methyl methacrylate unit is sometimes hydrolyzed to become a carboxyl group, and the carboxyl group is preferably restored to the original methyl methacrylate unit by an esterification reaction treated with an esterifying agent. As the esterifying agent, there is no particular limitation as long as it is within the range that can exert the effect of the present application, and dimethyl carbonate and the like can be preferably used. In addition, in addition to the esterifying agent, tertiary amines such as trimethylamine, triethylamine, and tributylamine can also be used in combination as a catalyst.
[0068] In the methacrylic acid copolymer (a) of the present invention, the ratio of the structural unit (r) is 25 to 70% by mass, preferably 30 to 68% by mass, more preferably 35 to 65% by mass, and further preferably 40 to 60% by mass relative to the total structural units. From the viewpoints of heat resistance, thermal decomposition resistance, low water absorption, and molding processability of the obtained methacrylic acid copolymer, and the dimensional stability of the laminated substrate film, and the adhesion to the vapor-deposited layer, the ratio of the structural unit (r) is preferably within the above range.
[0069] The methacrylic copolymer (a) of the present invention may further contain an N-substituted or unsubstituted maleimide unit in addition to the structural unit (r) etc. The N-substituted or unsubstituted maleimide unit is a unit having an N-substituted or unsubstituted 2,5-pyrrolidinedione structure.
[0070] As the unit having an N-substituted or unsubstituted 2,5-pyrrolidinedione structure, a structural unit represented by formula (VI) can be mentioned.
[0071]
[0072] (In formula (VI), R 10 It is a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an organic group having 6 to 15 carbon atoms and containing an aromatic ring.
[0073] The structural unit represented by formula (VI) can be obtained by polymerizing a monomer mixture containing the monomer represented by formula (VI), polymerizing a monomer mixture containing maleic anhydride, and reacting the maleic anhydride monomer in the reaction product obtained by polymerizing the monomer mixture containing maleic anhydride with the monomer represented by R 3 The methacrylic acid-based copolymer is contained in the methacrylic acid-based copolymer by reaction with an imidizing agent represented by NH2.
[0074] The N-substituted or unsubstituted maleimide unit can be obtained by the method described in Japanese Patent Publication No. 61-026924, Japanese Patent Publication No. 7-042332, Japanese Patent Publication No. 9-100322, Japanese Patent Publication No. 2001-329021, etc., specifically, by reacting an imidizing agent such as ammonia, methylamine, ethylamine, n-propylamine, isopropylamine, n-butylamine, isobutylamine, tert-butylamine, n-hexylamine, etc., an amine containing an aliphatic hydrocarbon group, aniline, toluidine, trichloroaniline, etc., an amine containing an alicyclic hydrocarbon group, such as cyclohexylamine, urea, 1,3-dimethylurea, 1,3-diethylurea, 1,3-dipropylurea, etc., with a maleic anhydride unit. Among them, methylamine is preferred.
[0075] The methacrylic copolymer (a) of the present invention may contain a lactone ring unit as a structural unit derived from other vinyl monomer units in addition to the structural unit (r) and the like. The lactone ring unit is a structural unit containing a >CH-OC(=O)- group in the ring structure. The number of ring constituent elements of the structural unit containing a >CH-OC(=O)- group in the ring structure is preferably 4 to 8, more preferably 5 to 6, and most preferably 6. As the structural unit containing a >CH-OC(=O)- group in the ring structure, lactone diyl structural units such as β-propiolactone diyl structural unit, γ-butyrolactone diyl structural unit, and δ-valerolactone diyl structural unit can be cited. The structural unit containing a >CH-OC(=O)- group in the ring structure can be obtained, for example, by intramolecular cyclization of a polymer having a hydroxyl group and an ester group using the hydroxyl group and the ester group. It should be noted that ">C" in the formula means that there are two bonds on the carbon atom C.
[0076] For example, as the δ-valerolactone diyl structural unit, there can be mentioned a structural unit represented by the formula (IV).
[0077]
[0078] In formula (IV), R 6 , R 7 and R 8Each independently represents a hydrogen atom or an organic group having 1 to 20 carbon atoms, preferably a hydrogen atom or an organic group having 1 to 10 carbon atoms, and more preferably a hydrogen atom or an organic group having 1 to 5 carbon atoms. Here, the organic group is not particularly limited as long as it has 1 to 20 carbon atoms, and examples thereof include a linear or branched alkyl group, a linear or branched aryl group, an -OCOCH3 group, a -CN group, etc. The organic group may contain heteroatoms such as an oxygen atom. R 6 and R 7 Preferably, methyl, R 8 Preferred is a hydrogen atom.
[0079] The lactone ring unit can be included in the methacrylic acid-based copolymer by the methods described in JP-A-2000-230016, JP-A-2001-151814, JP-A-2002-120326, JP-A-2002-254544, JP-A-2005-146084, etc., for example, by intramolecular cyclization of a structural unit derived from 2-(hydroxyalkyl)acrylate and a structural unit derived from methyl (meth)acrylate.
[0080] The methacrylic acid copolymer (I) of the present invention may further contain a glutaric anhydride unit as a structural unit derived from other vinyl monomer units in addition to the structural unit (r). The glutaric anhydride unit is a unit having a 2,6-dioxodihydropyrandiyl structure. As the unit having a 2,6-dioxodihydropyrandiyl structure, a structural unit represented by formula (V) can be cited.
[0081]
[0082] In formula (V), R 9 Each independently represents a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, and is preferably a methyl group.
[0083] The unit having a 2,6-dioxodhidropyrandiyl structure can be included in the methacrylic acid-based copolymer by the methods described in JP-A-2007-197703 and JP-A-2010-96919, for example, by intramolecular cyclization of two adjacent structural units derived from (meth)acrylic acid, intramolecular cyclization of a structural unit derived from (meth)acrylic acid and a structural unit derived from methyl (meth)acrylate, and the like.
[0084] The methacrylic copolymer (a) of the present invention may contain other vinyl monomer units copolymerizable with the methyl methacrylate unit. The other vinyl monomer units may be selected from materials appropriately according to the properties required of the methacrylic copolymer (a). When properties such as thermal stability, fluidity, chemical resistance, optical properties, and compatibility with other resins are particularly required, at least one selected from the group consisting of acrylic ester monomer units, aromatic vinyl monomer units other than styrene and α-methylstyrene, and vinyl cyanide monomer units is suitable.
[0085] Among the monomers constituting the above-mentioned monomer units, at least one selected from the group consisting of methyl acrylate, ethyl acrylate, and acrylonitrile is preferred from the viewpoint of availability.
[0086] Examples of other vinyl monomer units copolymerizable with methyl methacrylate include methacrylic acid amide units represented by the following formula (A) and 2-(hydroxyalkyl)acrylate units represented by the following formula (B).
[0087]
[0088] (Where R 3 R is a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an organic group having 6 to 15 carbon atoms and containing an aromatic ring, preferably a hydrogen atom, a methyl group, an n-butyl group, a cyclohexyl group, or a benzyl group, and more preferably a methyl group, an n-butyl group, or a cyclohexyl group. 4 and R 5 Each independently represents a hydrogen atom or an organic group having 1 to 20 carbon atoms, preferably a hydrogen atom or an organic group having 1 to 10 carbon atoms, and more preferably a hydrogen atom or an organic group having 1 to 5 carbon atoms. Here, the organic group is not particularly limited as long as it has 1 to 20 carbon atoms, and examples thereof include a linear or branched alkyl group, a linear or branched aryl group, an -OCOCH3 group, a -CN group, and the like. The organic group may contain heteroatoms such as an oxygen atom. R 4 Preferably, methyl, R 5 Preferably it is a hydrogen atom.)
[0089] In the methacrylic copolymer (a) of the present invention, the ratio of other vinyl monomer units copolymerizable with methyl methacrylate units is preferably 0 to 20% by mass, more preferably 0 to 15% by mass, and further preferably 0 to 10% by mass relative to all structural units. A methacrylic copolymer in which the ratio of other vinyl monomer units copolymerizable with methyl methacrylate units is greater than 20% by mass has reduced heat resistance and rigidity. It should be noted that the ratio of each monomer unit can be adjusted by 1 H-NMR, 13C-NMR, infrared spectroscopy, etc.
[0090] The weight average molecular weight (Mw) of the methacrylic copolymer (a) of the present invention is preferably 40,000 to 250,000, more preferably 50,000 to 200,000, and further preferably 60,000 to 180,000. When Mw is 40,000 or more, the methacrylic resin composition (I) of the present invention has excellent impact resistance. When Mw is 250,000 or less, the fluidity of the methacrylic resin composition (I) of the present invention is improved, and the molding processability is improved.
[0091] The weight average molecular weight (Mw) is a value calculated by converting a chromatogram measured by gel permeation chromatography into a molecular weight of standard polystyrene.
[0092] The glass transition temperature of the methacrylic copolymer (a) of the present invention is preferably 135°C or higher, more preferably 140°C, and further preferably 145°C. The upper limit is not particularly limited, but is preferably 170°C.
[0093] In this specification, "glass transition temperature (Tg)" is measured according to JIS K7121. Specifically, the temperature is raised to 250°C once, then cooled to room temperature, and then raised from room temperature to 250°C at a rate of 10°C / min, and a DSC curve is measured under such conditions. The midpoint obtained from the DSC curve measured at the second heating is obtained as the "glass transition temperature (Tg)".
[0094] The melt flow rate (hereinafter referred to as "MFR") of the methacrylic copolymer (a) of the present invention is preferably in the range of 1.0 to 30 g / 10 minutes. The lower limit of the MFR is more preferably 1.5 g / 10 minutes or more, and further preferably 2.0 g / 10 minutes. In addition, the upper limit of the MFR is more preferably 25 g / 10 minutes or less, and further preferably 20 g / 10 minutes or less. When the MFR is in the range of 1.0 to 30 g / 10 minutes, the stability of heated melt molding is good. It should be noted that the MFR of the methacrylic copolymer (a) in this specification refers to the value measured at a temperature of 230°C and a load of 3.8 kg using a melt indexer according to JIS K7210.
[0095] The saturated water absorption rate of the methacrylic acid copolymer (a) of the present invention can be measured under the following conditions. The methacrylic acid copolymer is formed into a sheet with a thickness of 1.0 mm by press molding. A 50 mm × 50 mm test piece is cut out from the center of the obtained pressed sheet and dried in a 90°C dryer for more than 16 hours. The dried test piece is cooled to room temperature in a dryer, and then the weight is measured to 0.1 mg, and the weight is set as the initial weight W0. The test piece is immersed in distilled water at 23°C. After immersion for 24 hours, the test piece is taken out of the water, and all the moisture on the surface is wiped off with a clean and dry cloth or filter paper. Within 1 minute after being taken out of the water, weigh the test piece again to 0.1 mg. The test piece is immersed again, and the weight is measured again by the same method as above after 24 hours. The weight of the test piece when the weight change rate reaches within 0.02% of W0 is set as the saturated weight W S The saturated water absorption rate can be calculated by formula (1).
[0096] Saturated water absorption rate = [(W S -W0) / W0]×100 (1)
[0097] The saturated water absorption is preferably 3.0% by mass or less, more preferably 2.7% by mass or less, and further preferably 2.5% by mass or less.
[0098] [Methacrylic resin]
[0099] The methacrylic resin composition (I) of the present invention may contain a methacrylic resin. The content of the methacrylic resin is preferably 1 to 49% by mass, more preferably 5 to 40% by mass, and further preferably 10 to 30% by mass. The methacrylic resin composition (I) of the present invention improves fluidity by containing a methacrylic resin.
[0100] The methacrylic resin is a resin containing a structural unit derived from methacrylate. Examples of the methacrylate include methyl methacrylate (hereinafter referred to as "MMA"), ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, pentyl methacrylate, hexyl methacrylate, heptyl methacrylate, 2-ethylhexyl methacrylate, nonyl methacrylate, decyl methacrylate, dodecyl methacrylate and other alkyl methacrylates; 1-methylcyclopentyl methacrylate, cyclohexyl methacrylate, cycloheptyl methacrylate, cyclooctyl methacrylate, tricyclo[5.2.1.0]methacrylate. 2,6] cycloalkyl methacrylates such as decyl-8-yl ester; aryl methacrylates such as phenyl methacrylate; aryl methacrylates such as benzyl methacrylate; etc., from the viewpoint of availability, MMA, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate and tert-butyl methacrylate are preferred, and MMA is most preferred. Methacrylates can be used alone or in combination of two or more. The content of the structural unit derived from methacrylate in the methacrylic resin is preferably 90% by mass or more, more preferably 95% by mass or more, and further preferably 98% by mass or more, and may be only structural units derived from methacrylate.
[0101] The lower limit of the syndiotacticity (rr) of the methacrylic resin in terms of triad is preferably 56% or more, more preferably 57% or more, and even more preferably 58% or more. When the lower limit of the content of this structure is 56% or more, the methacrylic resin composition (I) of the present invention has excellent heat resistance.
[0102] Here, the syndiotacticity (rr) calculated on a triad basis (hereinafter sometimes referred to as "syndiotacticity (rr)") is the ratio of two chains (diads) possessed by a chain of three consecutive structural units (triad) being both racemic (denoted as rr). It should be noted that, among the chains (diads) of structural units in a polymer molecule, chains having the same stereo configuration are called meso, and chains having opposite stereo configurations are called racemo, and are denoted as m and r, respectively.
[0103] The syndiotacticity (rr) (%) of the methacrylic resin can be measured in deuterated chloroform at 30°C. 1 H-NMR spectrum, from which the area (Y) of the region of 0.6 to 0.95 ppm and the area (Z) of the region of 0.6 to 1.35 ppm when tetramethylsilane (TMS) was set to 0 ppm were measured, and calculated by the formula: (Y / Z)×100.
[0104] The weight average molecular weight (hereinafter referred to as "Mw") of the methacrylic resin is preferably 40000 to 500000, more preferably 60000 to 300000, and even more preferably 80000 to 200000. When the Mw is 40000 or more, the methacrylic resin composition (I) of the present invention has excellent mechanical strength, and when the Mw is 500000 or less, the fluidity becomes good.
[0105] The glass transition temperature of the methacrylic resin is preferably 100° C. or higher, more preferably 105° C. or higher, and further preferably 110° C. or higher. When the glass transition temperature is 100° C. or higher, the methacrylic resin composition (I) of the present invention has excellent heat resistance.
[0106] The saturated water absorption of the methacrylic resin in water at 23° C. is preferably 2.5% by mass or less, more preferably 2.3% by mass or less, and even more preferably 2.1% by mass or less. When the saturated water absorption is 2.5% by mass or less, the methacrylic resin composition (I) of the present invention has excellent moisture resistance and can suppress warping of the laminate due to moisture absorption.
[0107] The MFR of the methacrylic resin is preferably in the range of 1 to 20 g / 10 minutes. The lower limit of the MFR is more preferably 1.2 g / 10 minutes or more, and further preferably 1.5 g / 10 minutes or more. In addition, the upper limit of the MFR is more preferably 15 g / 10 minutes or less, and further preferably 10 g / 10 minutes or less. When the MFR is in the range of 1 to 10 g / 20 minutes, the stability of the heated melt molding is good.
[0108] [Methacrylic resin composition (I)]
[0109] The glass transition temperature of the methacrylic resin composition (I) of the present invention is 135° C. or higher, preferably 140° C., more preferably 145° C., and the upper limit is not particularly limited, but is preferably 170° C. When the glass transition temperature is 135° C. or higher, the dimensional stability of the laminated substrate film for vapor deposition of the present invention is good.
[0110] The melt flow rate (hereinafter referred to as "MFR") of the methacrylic resin composition (I) of the present invention is preferably in the range of 1.0 to 30 g / 10 minutes. The lower limit of the MFR is more preferably 1.5 g / 10 minutes or more, and further preferably 2.0 g / 10 minutes. In addition, the upper limit of the MFR is more preferably 25 g / 10 minutes or less, and further preferably 20 g / 10 minutes or less. When the MFR is in the range of 1.0 to 30 g / 10 minutes, the stability of heat-melt molding is good.
[0111] The saturated water absorption of the methacrylic resin composition (I) of the present invention is preferably 3.0% by mass or less, more preferably 2.5% by mass or less, and further preferably 2.0% by mass or less. When the saturated water absorption is 3.0% by mass or less, the dimensional stability of the laminated substrate film for vapor deposition of the present invention is good.
[0112] The methacrylic resin composition (I) of the present invention may contain a filler as required within the range not impairing the effects of the present invention. Examples of fillers include calcium carbonate, talc, carbon black, titanium oxide, silica, clay, barium sulfate, magnesium carbonate, etc. The amount of filler that may be contained in the resin composition of the present invention is preferably 3% by mass or less, more preferably 1.5% by mass or less.
[0113] The methacrylic resin composition (I) of the present invention may contain other polymers within the range not impairing the effects of the present invention. Examples of other polymers include polyolefin resins such as polyethylene, polypropylene, polybutene-1, poly-4-methylpentene-1, and polynorbornene; ethylene ionomers; styrene resins such as polystyrene, styrene-maleic anhydride copolymer, high-impact polystyrene, AS resin, ABS resin, AES resin, AAS resin, ACS resin, and MBS resin; methyl methacrylate-styrene copolymers; polyester resins such as polyethylene terephthalate and polybutylene terephthalate; nylon 6, nylon 66, and polyamide elastomers; Polyamide; polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, ethylene-vinyl alcohol copolymer, polyacetal, polyvinylidene fluoride, polyurethane, phenoxy resin, modified polyphenylene ether, polyphenylene sulfide, silicone modified resin; silicone rubber; acrylic multilayer copolymer elastomer; acrylic thermoplastic elastomers such as diblock copolymers and triblock copolymers of methyl methacrylate polymer block-n-butyl acrylate polymer block; styrene thermoplastic elastomers such as SEPS, SEBS, and SIS; olefin rubbers such as IR, EPR, and EPDM, etc. The amount of other polymers that can be contained in the methacrylic resin composition (I) of the present invention is preferably 10% by mass or less, more preferably 5% by mass or less, and most preferably 0% by mass.
[0114] The methacrylic resin composition (I) of the present invention may contain additives such as antioxidants, heat degradation inhibitors, ultraviolet absorbers, light stabilizers, lubricants, mold release agents, polymer processing aids, antistatic agents, flame retardants, dyes / pigments, light diffusers, organic pigments, matting agents, and phosphors within a range that does not impair the effects of the present invention.
[0115] These additives can be used alone or in combination of two or more. In addition, these additives can be added to the polymerization reaction solution when manufacturing the methacrylic copolymer (a), can be added to the manufactured methacrylic copolymer (a), and can also be added when preparing the methacrylic resin composition (I) of the present invention. From the viewpoint of suppressing the poor appearance of the molded body, the total amount of the additives contained in the methacrylic resin composition (I) of the present invention is preferably 7% by mass or less, more preferably 5% by mass or less, and further preferably 4% by mass or less relative to the methacrylic resin composition (I).
[0116] The preparation method of the methacrylic resin composition (I) of the present invention is not particularly limited. For example, a method of polymerizing a monomer mixture containing methyl methacrylate and the like in the presence of a methacrylic resin to generate a methacrylic copolymer (a) and a method of melt-kneading the methacrylic copolymer (a) and the methacrylic resin can be cited. During melt-kneading, other polymers and additives can be mixed as needed, or the methacrylic copolymer (a) can be mixed with other polymers and additives and then mixed with the methacrylic resin, or the methacrylic resin can be mixed with other polymers and additives and then mixed with the methacrylic copolymer (a), or other methods can be used. Kneading can be carried out using a known mixing device or kneading device such as a kneader, an extruder, a mixing roll, a Banbury mixer, etc. Among them, a twin-screw extruder is preferred.
[0117] [Resin composition (T)]
[0118] The resin composition (T) used in the vapor deposition laminated substrate film of the present invention contains a thermoplastic resin (b). The thermoplastic resin (b) can be appropriately selected according to the purpose of the metal vapor deposition laminated film obtained using the vapor deposition laminated substrate film of the present invention, without particular limitation. For example, methacrylic resins, polyester resins, polycarbonate resins, polycyclic olefin resins, ABS resins, AAS resins and other styrene resins, polyvinylidene fluoride resins, etc. can be listed. From the viewpoint of transparency and formability, polycarbonate resins are preferred.
[0119] The polycarbonate resin is preferably obtained by copolymerizing a dihydric phenol such as bisphenol A and a carbonate precursor.
[0120] The Mw of the polycarbonate resin is preferably in the range of 10000 to 100000, and more preferably in the range of 20000 to 70000. When the Mw is 10000 or more, the impact resistance and heat resistance of the laminated substrate film for vapor deposition of the present invention are excellent, and when the Mw is 100000 or less, the molding processability of the polycarbonate resin is excellent, and the productivity of the laminated substrate film for vapor deposition of the present invention can be improved.
[0121] The polycarbonate resin may be a commercially available product, and preferably, for example, "SD POLYCA (registered trademark)" manufactured by Sumika Polycarbonate, "Iupilon / Novarex (registered trademark)" manufactured by Mitsubishi Engineering-Plastics Corporation, "TARFLON (registered trademark)" manufactured by Idemitsu Kosan Co., Ltd., and "Panlite (registered trademark)" manufactured by Teijin Chemicals Ltd. can be used.
[0122] The polycarbonate resin may contain other polymers within the range that does not impair the effects of the present invention. As the other polymers, methacrylic resins and polymers similar to other polymers that the methacrylic resin composition (I) may contain may be used. These other polymers may be used alone or in combination.
[0123] The content of these other polymers in the resin composition (T) is preferably 15% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less.
[0124] The resin composition (T) may contain various additives as required. As additives, the same additives as those that may be contained in the methacrylic resin composition (I) may be used. The content of these additives may be appropriately set within the range that does not impair the effect of the present invention. In the case of polycarbonate, the content of the antioxidant is preferably 0.01 to 1 part by mass, the content of the ultraviolet absorber is preferably 0.01 to 3 parts by mass, the content of the light stabilizer is preferably 0.01 to 3 parts by mass, the content of the lubricant is preferably 0.01 to 3 parts by mass, and the content of the dye / pigment is preferably 0.01 to 3 parts by mass.
[0125] The glass transition temperature of the resin composition (T) used in the present invention is preferably 120 to 160°C. In addition, the glass transition temperature of the resin composition (T) is preferably the same as the glass transition temperature of the methacrylic resin composition (I). Specifically, the absolute value of the difference between the glass transition temperature of the resin composition (T) and the glass transition temperature of the methacrylic resin composition (I) |ΔTg| is preferably 15°C or less, more preferably 10°C or less. If |ΔTg| is 15°C or less, the effect of suppressing the occurrence of warping of the laminated substrate film for vapor deposition under high temperature and high humidity is higher.
[0126] The saturated water absorption of the resin composition (T) used in the present invention in 80°C water is preferably 0.1 to 1.0% by mass. In addition, the saturated water absorption of the resin composition (T) is preferably the same as the saturated water absorption of the methacrylic resin composition (I). Specifically, the absolute value of the difference between the saturated water absorption of the resin composition (T) and the saturated water absorption of the methacrylic resin composition (I) |Δ saturated water absorption| is preferably 4.5% by mass or less, more preferably 4.0% by mass or less. If the difference in saturated water absorption between the two resins is 4.5% by mass or less, the effect of suppressing the occurrence of warping under high temperature and high humidity of the laminate is higher.
[0127] The MFR of the resin composition (T) used in the present invention is preferably in the range of 1 to 30 g / 10 minutes, more preferably in the range of 3 to 20 g / 10 minutes, and further preferably in the range of 5 to 10 g / 10 minutes. If the MFR is in the range of 1 to 30 g / 10 minutes, the stability of heat-melt molding is good.
[0128] In addition, the MFR of the resin composition (T) in this specification refers to the value measured under the conditions of a temperature of 300° C. and a load of 1.2 kg using a melt indexer.
[0129] [Laminated substrate film for vapor deposition]
[0130] The laminated substrate film for vapor deposition of the present invention comprises a layer formed of a methacrylic resin composition (I) and a layer formed of a resin composition (T). The laminated substrate film for vapor deposition of the present invention may have a layer formed of a methacrylic resin composition (I) and a layer formed of a resin composition (T), each of which is one layer, or may have a layer formed of a methacrylic resin composition (I) and / or a layer formed of a resin composition (T), each of which is two or more layers.
[0131] The laminated substrate film for vapor deposition of the present invention may further have a layer (other resin layer) formed of other resins in addition to the layer formed of the methacrylic resin composition (I) and the layer formed of the resin composition (T). The resin contained in the other resin layer may include: various thermoplastic resins other than the methacrylic resin composition (I) and the resin composition (T); thermosetting resins; energy ray curing resins; etc.
[0132] Examples of the other resin layer include a scratch-resistant layer, an antistatic layer, an antifouling layer, a friction-reducing layer, an antiglare layer, an antireflection layer, an adhesive layer, an impact strength-imparting layer, and an anchor layer.
[0133] These other resin layers may be one layer or two or more layers. In addition, when these other resin layers are two or more layers, they may be composed of the same resin or different resins. In the laminated substrate film for vapor deposition of the present invention, the arrangement order of the other resin layers is not particularly limited, and they may be the surface or the inner layer.
[0134] From the viewpoint of maintaining an excellent appearance and producing with good productivity, the thickness of the vapor deposition laminated substrate film of the present invention is preferably in the range of 0.03 to 0.5 mm, more preferably 0.05 to 0.4 mm, and even more preferably 0.07 to 0.3 mm.
[0135] The thickness of the layer formed of the methacrylic resin composition (I) in the vapor deposition laminated substrate film of the present invention is preferably in the range of 0.01 to 0.1 mm, more preferably in the range of 0.015 to 0.09 mm, and further preferably in the range of 0.02 to 0.08 mm. If the thickness is less than 0.01 mm, the scratch resistance and weather resistance may be insufficient. In addition, if the thickness exceeds 0.1 mm, the impact resistance may be insufficient.
[0136] The thickness of the layer formed by the resin composition (T) in the vapor deposition laminated substrate film of the present invention is preferably in the range of 0.02 to 0.4 mm, more preferably in the range of 0.035 to 0.31 mm, and further preferably in the range of 0.08 to 0.27 mm. From the viewpoint of impact resistance and productivity, the thickness of the layer formed by the resin composition (T) is preferably within the above range.
[0137] The thickness of the layer formed of the methacrylic resin composition (I) in the vapor deposition laminated substrate film of the present invention is preferably in the range of 2 to 20%, more preferably in the range of 3 to 17%, and further preferably in the range of 4 to 15% relative to the thickness of the vapor deposition laminated substrate film. From the viewpoint of scratch resistance, weather resistance and impact resistance, the thickness of the layer formed of the methacrylic resin composition (I) is preferably within the above range.
[0138] The thickness of the layer formed by the resin composition (T) in the vapor deposition laminated substrate film of the present invention is preferably in the range of 80 to 98%, more preferably in the range of 83 to 97%, and further preferably in the range of 85 to 96% relative to the thickness of the laminate. From the viewpoint of impact resistance and weather resistance, the ratio of the thickness of the layer formed by the resin composition (T) to the thickness of the vapor deposition laminated substrate film of the present invention is preferably within the above range.
[0139] When the vapor deposition laminated substrate film of the present invention comprises only a layer formed of the methacrylic resin composition (I) and a layer formed of the resin composition (T), the layer formed of the methacrylic resin composition (I) is denoted as (1) and the layer formed of the resin composition (T) is denoted as (2). Examples of the lamination order of the vapor deposition laminated substrate film of the present invention include (1)-(2), (1)-(2)-(1), (2)-(1)-(2), (1)-(2)-(1)-(2)-(1), and the like. From the viewpoint of improving scratch resistance, it is preferred that the lamination be performed in such a manner that at least one surface becomes a layer formed of the methacrylic resin composition (I), such as (1)-(2), (1)-(2)-(1), (1)-(2)-(1)-(2)-(1).
[0140] In addition, when the vapor deposition laminated substrate film of the present invention has another resin layer, when the other resin layer is indicated as (3), the lamination order of the laminated body of the present invention may be (1)-(2)-(3), (3)-(1)-(2), (3)-(1)-(2)-(3), (3)-(1)-(2)-(1)-(3), (1)-(2)-(3)-(2)-(1), etc. For example, when (3) is an anchor layer, when the anchor layer is indicated as (3'), the lamination order of the vapor deposition laminated substrate film of the present invention is preferably (3')-(1)-(2), (3')-(1)-(2)-(3'), (3')-(1)-(2)-(1)-(3'), etc., in which at least one surface is the anchor layer.
[0141] In addition, when the vapor deposition laminated substrate film of the present invention has another resin layer different from (3) in addition to (3), when the other resin layer different from (3) is marked as (4), the stacking order of the laminated body of the present invention can be listed as (1)-(2)-(3)-(4), (4)-(3)-(1)-(2), (4)-(3)-(1)-(2)-(3), (4)-(1)-(2)-(3), (4)-(3)-(1)-(2)-(3)-(4), (4)-(3)-(1)-(2)-(1)-(3)-(4), etc.
[0142] From the viewpoint of suppressing the occurrence of warping under high temperature and high humidity, the deposition layered substrate film of the present invention preferably has a symmetrical lamination order in the thickness direction, and more preferably, the thickness of each layer is also symmetrical.
[0143] The total light transmittance of the vapor deposition laminated substrate film of the present invention is preferably 80% or more, more preferably 85% or more, and further preferably 90% or more. With a total light transmittance of 80% or more, the appearance quality of the vapor deposition laminated substrate film obtained in the present invention is excellent. The total light transmittance can be measured by a method based on JIS K7105.
[0144] The wetting tension of the surface of the layer formed by the methacrylic resin composition (I) of the vapor deposition laminated substrate film of the present invention is preferably 38mN / m or more, more preferably 39mN / m or more, and further preferably 40mN / m or more. When the wetting tension of the surface is at least 38mN / m or more, the bonding strength between the vapor deposition laminated substrate film of the present invention and the vapor deposition layer is improved. In order to adjust the wetting tension of the surface, for example, corona discharge treatment, ozone blowing, ultraviolet irradiation, flame treatment, chemical reagent treatment, and other previously known surface treatments can be implemented. The wetting tension can be measured by a method based on JIS K6768.
[0145] The method for producing the laminated substrate film for vapor deposition of the present invention is not particularly limited, and the lamination of the layer formed by the methacrylic resin composition (I) and the layer formed by the resin composition (T) is usually preferably performed by multilayer molding. As multilayer molding, multilayer extrusion molding, multilayer blow molding, multilayer press molding, multicolor injection molding, insert injection molding and other lamination molding methods can be cited, and from the viewpoint of productivity, multilayer extrusion molding is preferred.
[0146] Examples of a method for further laminating another resin layer include a method of performing multilayer molding by the above method together with a layer formed from the methacrylic resin composition (I) and a layer formed from the resin composition (T); a method of applying another fluid resin on the surface of a previously produced layer formed from the methacrylic resin composition (I) or a layer formed from the resin composition (T) and then drying or curing the layer; and a method of laminating a previously produced layer formed from the methacrylic resin composition (I) or a layer formed from the resin composition (T) with an adhesive layer interposed therebetween.
[0147] The multilayer extrusion molding method is not particularly limited, and a known multilayer extrusion molding method used in the production of a multilayer laminate of a thermoplastic resin can be preferably adopted, and molding is more preferably performed by an apparatus having a flat T-die and a polished roll with a mirror-finished surface.
[0148] As the T-die method in this case, a feed head method in which the methacrylic resin composition (I) and the resin composition (T) in a heated and molten state are stacked before flowing into the T-die, a multi-manifold method in which the resin composition (I) and the resin composition (T) are stacked inside the T-die, etc. From the viewpoint of improving the smoothness of the interface between the layers constituting the laminated substrate film for vapor deposition, the multi-manifold method is preferred.
[0149] In addition, as the polishing roller in this case, a metal roller, an elastic roller having a metal film on the outer periphery (hereinafter, sometimes referred to as a metal elastic roller), etc. can be listed. As the metal roller, there is no particular limitation as long as it is highly rigid, and examples thereof include a drilled roller, a spiral roller, etc. There is no particular limitation on the surface state of the metal roller, and for example, it can be a mirror surface, or it can be a pattern, a concave-convex surface, etc. The metal elastic roller is composed of, for example, a shaft roller that is roughly cylindrical and freely rotatable, a cylindrical metal film that is arranged to cover the outer periphery of the shaft roller and is in contact with the film-like object, and a fluid that is sealed between these shaft rollers and the metal film, and the metal elastic roller exhibits elasticity through the fluid. The shaft roller is not particularly limited, and for example, it is composed of stainless steel, etc. The metal film is composed of, for example, stainless steel, etc., and its thickness is preferably about 2 mm to about 5 mm. The metal film preferably has buckling properties, flexibility, etc., and preferably has a seamless structure without a welded joint. The metal elastic roller having such a metal thin film has excellent durability and can be processed in the same manner as a normal mirror-finished roller if the metal thin film is mirror-finished, and can transfer the shape if a pattern or projections and depressions are given to the metal thin film, so it is easy to use.
[0150] The methacrylic resin composition (I) and the resin composition (T) are preferably melt-filtered by a filter before and / or during multilayer forming. By using each resin composition after melt filtration for multilayer forming, a laminate with few defects caused by foreign matter and gel can be obtained. The filter material of the filter used is not particularly limited and can be appropriately selected according to the use temperature, viscosity, and filtration accuracy. For example, non-woven fabrics composed of glass fibers, etc. can be used; cellulose films impregnated with phenolic resins; metal fiber non-woven fabric sintered films; metal powder sintered films; metal mesh; or they can be used in combination. Among them, from the viewpoint of heat resistance and durability, it is preferred to use multiple layers of metal fiber non-woven fabric sintered films.
[0151] The filtration accuracy of the filter is not particularly limited, but is preferably 30 μm or less, more preferably 10 μm or less, and further preferably 5 μm or less.
[0152] Hereinafter, the anchor layer will be described in detail as an example of a layer formed from another resin composition. The anchor layer is provided to improve the adhesion between the layer formed from the methacrylic resin composition (I) and the vapor-deposited layer.
[0153] The anchoring layer is not particularly limited. For example, as long as the anchoring layer has good adhesion to the layer formed by the methacrylic resin composition (I) and good acceptance of the material constituting the vapor deposition layer, it can be an acrylic resin, a nitrocellulose resin, a polyurethane resin (including a resin obtained by curing the polyol resin as a main agent and an isocyanate resin as a curing agent), an acrylic urethane resin (including a resin obtained by curing the polyol resin as a main agent and an isocyanate resin as a curing agent), a polyester resin, a styrene-maleic acid resin, a chlorinated PP resin, etc. Among them, from the viewpoint of better adhesion of the obtained laminated film (laminated substrate film for vapor deposition, vapor deposition laminated film), the anchoring layer preferably contains an acrylic resin.
[0154] The acrylic resin is not particularly limited and may be included in the above-mentioned methacrylic resin category. The thickness of the anchor layer is preferably 0.1 to 3 μm. When the thickness of the anchor layer is within the above range, the layer formed of the methacrylic resin composition (I) of the laminated film has excellent adhesion to the vapor-deposited layer.
[0155] The anchoring layer can be given design by adding a colorant or a metallic pigment. For example, by adding a yellow pigment as a colorant, the film can present a golden appearance. The type and content of the colorant can be appropriately adjusted according to the desired metallic appearance. In addition, the anchoring layer can be given functions such as an antistatic effect by adding an antistatic agent. In addition, a curing agent having an isocyanate resin can be mixed in the anchoring layer. By mixing a curing agent having an isocyanate resin, the heat resistance, weather resistance, and water resistance of the obtained laminated film can be further improved.
[0156] The method for forming the anchor layer is not particularly limited. As an example, the anchor layer can be formed by applying a resin solution constituting the anchor layer dissolved in a suitable solvent (e.g., methyl ethyl ketone, toluene, ethyl acetate, etc.) onto the layer formed by the methacrylic resin composition (I) using a roll coater, followed by drying at about 80° C. to about 100° C. for 30 seconds to 1 minute.
[0157] [Vapor-deposited laminated film]
[0158] In the vapor-deposited laminated film of the present invention, in the case of a vapor-deposited laminated base film in which a layer formed by a methacrylic resin composition (I) is laminated on one surface of a layer formed by a resin composition (T), a vapor-deposited layer is provided on the surface on the side of the layer formed by the methacrylic resin composition (I), or in the case of a vapor-deposited laminated base film in which layers formed by a methacrylic resin composition (I) are laminated on both surfaces of a layer formed by a resin composition (T), a vapor-deposited layer is provided on either surface.
[0159] The vapor deposition layer is provided to impart various functions to the film, such as decoration, scratch resistance, antistatic, antifouling, friction reduction, antifogging, antiglare, light reflection prevention, high light reflection, adhesion, impact resistance, anti-adhesion, gas barrier, transparent conductivity, etc.
[0160] As the material constituting the vapor deposition layer, there is no particular limitation, and examples thereof include: elemental metal, elemental metalloid, inorganic compound, organic compound, etc. As the inorganic compound, oxides and oxynitrides of Si, Al, In, Sn, Zn, Ti, Cu, Ce, Ta, etc. are preferred. As the organic compound, an organic polymer compound is preferred. In addition, polysiloxane, polyparaxylene, polyurethane (diisocyanate / diol), polyurea (diisocyanate / diamine), polythiourea (dithioisocyanate / diamine), polythioether carbamate (bisethylene carbamate / dithiol), polyimine (diepoxy / primary amine), polypeptide amide (bis-azlactone / diamine), polyamide (diolefin / diamide) and other addition polymers, acrylate polymers, etc. can be used.
[0161] One or more vapor-deposited layers using at least one selected from these materials may be provided on one or both surfaces of the vapor-deposited laminated base film.
[0162] Vapor-deposited layers composed of silicon oxide, silicon oxynitride, aluminum oxide, etc. have excellent light transmittance and are suitable for optical applications.
[0163] Polysiloxane is formed by introducing vapor obtained by heating and evaporating hexamethyldisiloxane into a parallel plate plasma device using RF electrodes, and depositing on a substrate film while undergoing a polymerization reaction in the plasma. The vapor-deposited layer formed of polysiloxane can be easily hydrophilized by oxygen plasma, etc., has good adhesion to the inorganic vapor-deposited layer, and has excellent bending resistance.
[0164] For polyparaxylene, for example, polyparaxylene is heated and evaporated in a high vacuum, and the vapor is heated to 650°C to 700°C to thermally decompose polyparaxylene to generate free radicals. When the free radicals are introduced into a chamber provided with a substrate film, the free radicals are adsorbed on the substrate film and free radical polymerization is performed to form a polyparaxylene film. The vapor-deposited layer formed of polyparaxylene has excellent mechanical strength, thermal strength, chemical strength, etc.
[0165] The addition polymer is formed by, for example, depositing the above-mentioned monomers on a substrate film in a vacuum while performing addition polymerization. Among the addition polymers, polyurea is preferred from the viewpoints of transparency, material cost, and the like.
[0166] In order to impart the function of preventing light reflection, for example, a vapor deposited layer having a refractive index lower than that of the base film is disposed on the surface of the base film, or a vapor deposited layer having a high refractive index and a vapor deposited layer having a low refractive index are disposed in sequence on the surface of the base film.
[0167] In order to impart a gas barrier function, for example, a dense vapor-deposited layer (gas barrier vapor-deposited layer) is provided on the surface of the substrate film to such an extent that water molecules, oxygen molecules and other gas molecules to be blocked cannot penetrate. Examples of materials constituting the gas barrier vapor-deposited layer include: elemental metals such as aluminum, nickel, chromium, iron, cobalt, zinc, gold, silver, and copper, and metal alloys composed of their combinations; elemental metalloids such as silicon, germanium, and carbon (diamond-like carbon, graphite, etc.); oxides such as silicon oxide, aluminum oxide, magnesium oxide, indium oxide, calcium oxide, zirconium oxide, titanium oxide, boron oxide, zinc oxide, cerium oxide, hafnium oxide, and barium oxide; nitrides such as silicon nitride, aluminum nitride, boron nitride, and magnesium nitride; carbides such as silicon carbide; oxycarbides; nitrogen carbides; oxynitrides; oxynitrocarbides; sulfides, etc.
[0168] In order to impart a transparent conductive function, for example, an indium oxide film containing at least one of tin, germanium, zinc, gallium, and magnesium can be used.
[0169] Regarding the vapor-deposited layer containing indium, the obtained film has excellent formability and can be easily processed into various three-dimensional shapes, so it is also suitable for metal texture decoration. Indium can be contained in the form of oxides and nitrides. In addition to indium, various non-metals, metals, metal oxides and metal nitrides can also be contained.
[0170] The obtained vapor deposited layer can be analyzed using, for example, a surface analysis device such as a photoelectron spectrophotometer, an X-ray photoelectron spectrometer (XPS), or a secondary ion mass spectrometer (SIMS). These devices can analyze the vapor deposited layer in the thickness direction by ion etching.
[0171] The thickness of the vapor-deposited layer can be set according to the function to be imparted, preferably 5 to 2000 nm, more preferably 10 to 1500 nm, further preferably 20 to 1000 nm, and most preferably 30 to 500 nm. When the thickness of the vapor-deposited layer is within the above range, the vapor-deposited layer can easily balance its function with productivity and formability.
[0172] The deposited layer can be formed by a known deposition method, which includes physical deposition methods (PVD methods) such as vacuum deposition, sputtering, and ion plating, and chemical deposition methods (CVD methods) such as reduced pressure chemical deposition, catalytic chemical deposition, and plasma chemical deposition.
[0173] Among them, the vacuum vapor deposition method is preferred because of its high productivity. The vapor deposition conditions can be appropriately adopted according to the desired thickness of the vapor-deposited layer.
[0174] Before vapor deposition, the surface of the substrate film may be subjected to surface treatment within a range that does not impair the purpose of the present invention. Examples of surface treatment include: discharge treatment methods such as low-temperature plasma treatment and corona discharge treatment; chemical reagent treatment methods such as acid treatment, alkali treatment, and organic solvent treatment; treatment methods by applying a primer coating, etc. Carbonyl groups, carboxyl groups, hydroxyl groups, etc. can be added by discharge treatment methods, and polar groups such as amino groups, hydroxyl groups, and carbonyl groups can be added by chemical reagent treatment methods.
[0175] The vapor-deposited laminated film of the present invention may further have a coating film on the surface of the vapor-deposited layer. The coating film refers to a film formed by applying a coating composition, drying it as needed, and curing it. Various functions can be imparted by the coating film. As such functions, for example, decoration, scratch resistance, antistatic, antifouling, friction reduction, antifogging, anti-glare, light reflection prevention, high light reflection, adhesion, impact resistance, anti-adhesion, gas barrier, transparent conductivity, etc. can be cited. There is no particular limitation on the method of applying the coating composition, for example, methods such as roller coating, gravure coating, blade coating, dip coating, curtain coating, spray coating, and scraper bar coating can be used.
[0176] The metallic sheet of the present invention is formed by laminating a thermoplastic resin sheet as a backing material on the surface of the vapor-deposited layer of the vapor-deposited laminated film of the present invention. Here, there is no particular restriction on the resin constituting the thermoplastic resin sheet, and examples thereof include: ABS (acrylonitrile-butadiene-styrene copolymer) resin, polycarbonate resin, methacrylic resin, polyvinyl chloride resin, polyurethane resin, polyester resin, polyolefin resin, etc. In addition, there is no particular restriction on the thickness of the above-mentioned thermoplastic resin sheet, and it can be the thickness of the so-called film area. Specifically, the thickness of the above-mentioned thermoplastic resin sheet is usually 0.2 to 2 mm.
[0177] In the metallic sheet of the present invention, the vapor-deposited layer and the thermoplastic resin sheet are preferably laminated with an adhesive layer interposed therebetween. The presence of the adhesive layer can provide good adhesion between the vapor-deposited layer and the thermoplastic resin sheet, and can be suitably used as a metallic sheet.
[0178] The adhesive forming the above-mentioned adhesive layer can withstand the heating temperature during forming, and can be appropriately selected according to the type of metal vapor deposition layer and thermoplastic resin sheet in a manner that exhibits good adhesion. For example, one or more adhesives of various resins including polyurethanes, polyesters, polyethylenes, polyamides, polyvinyl chlorides, polychloroprenes, carboxylated rubbers, thermoplastic styrene-butadiene rubbers, acrylics, styrenes, celluloses, alkyds, polyvinyl acetates, ethylene-vinyl acetate copolymers, polyvinyl alcohols, epoxies, silicones, natural rubbers, synthetic rubbers, etc. are used. It should be noted that, considering the influence of metallic luster on color tone, additives such as pigments, dyes, metal powders, mica, etc. can be added to these adhesives for the purpose of adjusting the color tone.
[0179] The thickness of the adhesive layer is preferably 1 to 20 μm, more preferably 2 to 8 μm. If the thickness of the adhesive layer is less than 1 μm, the adhesive force may be insufficient, while if the thickness is greater than 20 μm, it takes a long time to dry the adhesive layer, which is not preferred in terms of process and has a disadvantageous tendency in terms of cost.
[0180] In addition, in the metallic sheet of the present invention, the metal vapor-deposited layer and the thermoplastic resin sheet are preferably laminated by dry lamination. Specifically, for example, the above-mentioned adhesive can be made into a solution or emulsion state using a solvent as needed, and it can be coated on the metal vapor-deposited layer or the thermoplastic resin sheet or both by a known means such as a gravure coater, a reverse coater, a die coater, a knife coater, a roll coater, etc., and dried appropriately.
[0181] The metallic molded product of the present invention is a molded product obtained by laminating the vapor-deposited laminated film or the metallic sheet of the present invention on the molded product in such a manner that the surface opposite to the vapor-deposited layer side is arranged on the surface side. Here, as the molded product to which the vapor-deposited laminated film or the metallic sheet is attached, for example, a molded product formed of a thermoplastic resin such as ABS resin, polycarbonate resin, methacrylic resin, polyvinyl chloride resin, polyurethane resin, polyester resin, polyolefin resin, etc. is preferably used.
[0182] In the metallic texture formed product of the present invention, the vapor-deposited layer and the formed product are preferably laminated with an adhesive layer sandwiched therebetween. The presence of the adhesive layer can provide good adhesion between the vapor-deposited layer and the formed product. Here, the type of adhesive forming the adhesive layer and the thickness of the adhesive layer are the same as those of the adhesive layer in the metallic texture sheet of the present invention, but are usually appropriately selected in a manner that the adhesive layer after drying does not have adhesiveness.
[0183] As methods for obtaining the metal texture molded product of the present invention, there can be listed: film (sheet) in-mold molding, lamination injection compression molding, film (sheet) insert molding, vacuum pressure molding, TOM (Three dimension Overlay Method: three-dimensional superposition method) molding, hot stamping molding, etc. Among them, the film (sheet) insert injection molding method can be advantageously adopted. The film (sheet) insert injection molding method is a method as follows: the vapor-deposited laminated film and the metal texture sheet are pre-formed by vacuum molding, pressure molding, etc., and then trimmed by a Thomson die cutter, etc., and then inserted into the injection molding mold, and molten resin is injected therein to form an injection molded product, and at the same time, the molded film and the metal texture sheet are bonded to the molded product. For more detailed content about the film (sheet) insert injection molding method, for example, it can be according to the previously known technology recorded in Japanese Patent Gazette No. 2005-254531, etc.
[0184] The vapor-deposited laminated film of the present invention can be used, for example, in automobile interior and exterior decoration, personal computer interior and exterior decoration, mobile terminal interior and exterior decoration, wearable terminal interior and exterior decoration, solar cell interior and exterior decoration, solar cell backplane, liquid crystal light guide plate, diffuser, backplane, reflector, polarizer protective film, phase difference film and other liquid crystal display film, surface protection film and other information equipment fields, optical fiber, optical switch, optical connector and other optical communication fields, automobile headlight, taillight lens, inner lens, instrument cover, automobile sunroof, glass window and other vehicle fields, glasses, corneal contact lens, endoscope lens, road sign, bathroom equipment, floor material, road light-transmitting plate, double-layer glass lens, skylight, carport, lighting lens, lighting cover, building material glue and other construction / building material fields, microwave cooking container (tableware), housing of home appliance, toys, sunglasses, stationery, solar concentrating film, etc. In addition, it can also be used as an alternative to the molded product using the transfer foil.
[0185] On the other hand, for the metallic texture formed product obtained by forming the vapor-deposited laminated film of the present invention, for example, the metallic texture formed product is a metallic texture billboard, an interior and exterior decorative component for a metallic texture vehicle, a metallic texture household appliance, a metallic texture entertainment product, a metallic texture building material, etc. Among them, the metallic texture formed product is suitable for use as an interior and exterior decorative component for a metallic texture vehicle. There is no particular restriction on the interior and exterior decorative components for metallic texture vehicles. If an example is cited, the interior and exterior decorative components for metallic texture vehicles are dashboard decorations and ornaments, audio panels, automobile air conditioning panels, steering wheel decorations, door interior panel decorations, electric window switch baffles, operating system handles, switches and caps or covers, radiator grilles, column decorations, rear door decorations, rearview mirror covers, outer panels, rear spoilers, inner or outer door handles, side window visors, wheel covers, electric two-wheeled vehicle covers, etc. Among them, the interior and exterior decorative components for metallic texture vehicles of the present embodiment are more suitable when applied to steering wheels, handles, etc.
[0186] Example
[0187] Hereinafter, the present invention will be described in more detail with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples.
[0188] The measurement of physical properties and the like was carried out by the following methods.
[0189] (Polymerization conversion rate)
[0190] A gas chromatograph GC-14A manufactured by Shimadzu Corporation was connected with INERTCAP1 (df = 0.4 μm, 0.25 mm I.D. × 60 m) manufactured by GL Sciences Inc. as a column, and analysis was performed under the following conditions, and calculations were performed based on the conditions.
[0191] Inlet temperature = 250°C
[0192] Detector temperature = 250°C
[0193] Temperature conditions: maintain at 60°C for 5 minutes → increase the temperature to 250°C at 10°C / min → maintain at 250°C for 10 minutes
[0194] (Composition of each unit of the precursor polymer)
[0195] pass 13 The carbon ratios of the phenyl group of the α-methylstyrene unit, the carbonyl group of the methyl methacrylate unit, the phenyl group of the styrene unit, and the carbonyl group of the maleic anhydride unit were determined by C-NMR, and the composition of each unit was calculated from the ratio.
[0196] (Weight average molecular weight)
[0197] The weight average molecular weight (Mw) of each resin obtained in the manufacturing example is determined by GPC (gel permeation chromatography). 4 mg of the resin to be measured is dissolved in 5 ml of tetrahydrofuran to prepare a sample solution. The temperature of the column oven is set to 40°C, and 20 μl of the sample solution is injected into the device under the condition of an eluent flow rate of 0.35 ml / min, and the chromatogram is measured. GPC measurement is performed on 10 points of standard polystyrene with a molecular weight in the range of 400 to 5000000, and a calibration curve showing the relationship between retention time and molecular weight is prepared. The Mw of the resin to be measured is determined based on the calibration curve. According to the chromatogram measured by GPC, the value equivalent to the molecular weight of the standard polystyrene is used as the molecular weight of the copolymer.
[0198] Equipment: GPC equipment HLC-8320 manufactured by Tosoh Corporation
[0199] Separation column: TSK guardcolum Super HZ-H, TSKgel HZM-M and TSK gel Super HZ4000 manufactured by Tosoh Corporation connected in series
[0200] Eluent: Tetrahydrofuran
[0201] Eluent flow rate: 0.35ml / min
[0202] Column temperature: 40°C
[0203] Detection method: Differential refractive index (RI)
[0204] (Composition of each unit in the methacrylic acid copolymer)
[0205] The composition of the α-methylstyrene unit and the styrene unit is the same as that of each unit of the precursor polymer.
[0206] use 1 The methacrylic acid copolymer was analyzed by H-NMR (manufactured by Bruker; trade name ULTRA SHIELD 400 PLUS). 1 H-NMR measurement was used to determine the content (mol%) of each monomer unit in the methacrylic copolymer, such as the imide unit (glutarimide and maleimide), methyl methacrylate unit, and aromatic vinyl (α-methylstyrene and styrene) unit, and the content (mol%) was converted into the content (weight%) using the molecular weight of each monomer unit. In addition, infrared spectrophotometer was used to measure the content (mol%) at 1700 cm -1 The absorption intensity of the peaks attributable to the carbonyl unit of maleimide and 1780 cm -1 The imidization ratio (R m). 13 The maleic anhydride amount (m) and imidization ratio (R) of the precursor polymer determined by C-NMR m ) The value calculated by the following formula is regarded as the amount of maleic anhydride (M) in the methacrylic acid copolymer.
[0207] Maleic anhydride amount (M) = m × (100-Rm) / 100
[0208] Furthermore, using an infrared spectrophotometer, the -1 The absorption intensity of the peak attributed to the carbonyl group of glutarimide and the peak at 1700 cm -1 The ratio of the glutarimide unit to the maleimide unit in the methacrylic copolymer was determined by using the absorption intensity of the peak attributable to the carbonyl unit of maleimide in the vicinity. 1 The contents of the glutarimide units and the maleimide units in the methacrylic acid-based copolymer were determined from the amount of the imide units in the methacrylic acid-based copolymer determined by H-NMR and the ratio of the glutarimide units to the maleimide units.
[0209] (Total transmittance; Tt)
[0210] The methacrylic resin composition obtained in the production example was press-formed into a sheet having a thickness of 3 mm. The total light transmittance of the press plate was measured using a haze meter (manufactured by Murakami Color Laboratory; trade name: HM-150) in accordance with JIS K7361-1.
[0211] (Glass transition temperature; Tg)
[0212] The methacrylic resin composition obtained in the manufacturing example was dissolved in chloroform, reprecipitated with methanol, and then the precipitated resin was vacuum dried at 100°C for more than 12 hours. The vacuum-dried resin was heated to 250°C once, cooled to room temperature, and then heated from room temperature to 200°C at 10°C / min using a differential scanning calorimeter (DSC-50 (product number) manufactured by Shimadzu Corporation) in accordance with JIS K7121. The DSC curve was measured under such conditions. The midpoint glass transition temperature obtained from the DSC curve measured at the second heating was used as the glass transition temperature in the present invention.
[0213] (1% thermogravimetric reduction temperature)
[0214] The methacrylic resin composition obtained in the preparation example was heated at 10°C / min in a nitrogen atmosphere using a thermogravimetric measuring apparatus (TGA-50 manufactured by Shimadzu Corporation), and the temperature at which the weight was reduced by 1% from 200°C was defined as the 1% thermogravimetric reduction temperature.
[0215] (Saturated water absorption)
[0216] The methacrylic resin composition obtained in the manufacturing example is press-formed and then cut to obtain a square test piece with a thickness of 3 mm and a side of 50 mm. The test piece is vacuum dried for 24 hours at a temperature of 80°C and 5 mmHg. Then, the test piece is cooled in a dryer. Take out the test piece from the dryer and immediately measure the mass (initial mass). Next, immerse the test piece in distilled water at 23°C. Take out the test piece from the water, wipe off the water attached to the surface, and measure the mass. Repeat the immersion in distilled water and mass measurement until the mass change disappears. The saturated water absorption rate is calculated according to the following formula from the mass (water absorption mass) when the mass change disappears and the initial mass.
[0217] Saturated water absorption rate (%) = [(water absorption mass - initial mass) / initial mass] × 100
[0218] (Unnotched Charpy Impact Strength)
[0219] The methacrylic resin composition obtained in the manufacturing example was press-formed and then cut to obtain a test piece with a thickness of 4 mm, a length of 80 mm, and a width of 10 mm. Each test piece was measured under the conditions of 23° C. and a relative humidity of 50% by a method based on the method described in JIS K7111-1 / 1eU. The measurement was performed 10 times, and the average value of the Charpy impact value was adopted.
[0220] (Melt Flow Rate; MFR)
[0221] The methacrylic resin composition obtained in the production example was dissolved in chloroform and reprecipitated with methanol, and the precipitated resin was vacuum dried at 100° C. for 12 hours or more. The vacuum dried resin was measured at 230° C. and 3.8 kg load according to JIS K7210.
[0222] (Wetting tension)
[0223] The methacrylic resin composition obtained in the production example was press-molded into a sheet having a thickness of 3 mm. The wetting tension was measured in accordance with JIS K6768 at 23° C. and a relative humidity of 50% using a mixed solution for wetting tension test (manufactured by Wako Pure Chemical Industries, Ltd.).
[0224] (Appearance)
[0225] The appearance of the vapor deposition laminated substrate films of Examples and Comparative Examples was visually observed, and the appearance was judged based on transparency, flow pattern due to poor flow, and the presence or absence of foaming due to thermal decomposition of the resin.
[0226] ◎: Transparent, no flow pattern or foaming
[0227] ×: Opaque, with flowing patterns and foaming
[0228] (Dimensional stability)
[0229] The laminated substrate films for vapor deposition of the examples and comparative examples were cut into rectangles with the long side parallel to the extrusion flow direction and the short side perpendicular to the extrusion flow direction, to prepare test pieces with a long side of 200 mm and a short side of 120 mm. The test pieces were placed on a platform in such a way that both ends of the test piece were in contact with the platform (i.e., in such a way that the test piece was convex upward), and the maximum value of the gap between the test piece and the platform was measured using a gap gauge as the initial warpage amount.
[0230] Next, each test piece was placed in a hot air dryer set at a temperature of 100°C for 1 hour, and then the test piece with the short side stopped by a clamp was hung in an environmental testing machine set at a temperature of 85°C and a relative humidity of 85%, and placed in this state for 72 hours, and then cooled and humidified for 120 hours at 23°C and a relative humidity of 50%. As a result, all the test pieces had a bow-shaped warp along the long side of the test piece with the layer formed by the methacrylic resin composition (I) as the outside and the layer formed by the resin composition (T) as the inside. The test piece with the bow-shaped warp was placed on the platform in a manner that the two end portions of the test piece were in contact with the platform (that is, in a manner that the test piece was convex upward), and the maximum value of the gap between the test piece and the platform was measured using a gap gauge as the warp amount under high temperature and high humidity. The warp change under high temperature and high humidity is calculated according to the following formula, and the quality of dimensional stability is judged according to the change.
[0231] Warpage change under high temperature and high humidity = Warpage under high temperature and high humidity - Initial warpage
[0232] ◎: Warpage change under high temperature and high humidity is less than 10 mm
[0233] ○: The warpage change under high temperature and high humidity is greater than 10mm and less than 20mm
[0234] ×: Warpage change under high temperature and high humidity is greater than 20 mm
[0235] (Softness)
[0236] The vapor deposition laminated substrate films of Examples and Comparative Examples were folded in half from the layer side formed from the methacrylic resin composition (I), and the presence or absence of cracks around the folds or broken parts of the films was visually checked and evaluated according to the following criteria.
[0237] ◎: No cracks were observed
[0238] ○: Slightly observed small cracks that can be ignored
[0239] ×: Cracks observed
[0240] (Adhesion to the vapor deposited layer)
[0241] SRC-10-D (manufactured by Japan Vacuum Technology Co., Ltd.) was used with a 4.5×10 -5 The three metals of aluminum, tin and indium were vacuum-deposited onto the layer formed of the methacrylic resin composition (I) of the laminated substrate film for vapor deposition of the embodiment and the comparative example. The film thickness of the vapor-deposited aluminum, tin and indium was set to a range of 500 to 1500 angstroms. A cutter was used to cut the vapor-deposited surface at 1 cm 2 100 grid-like cuts were made in the area, and the evaluation was performed by a Sellotape (registered trademark) peeling test.
[0242] ○: No peeling was observed in the vapor-deposited layer or less than 10 pieces of peeling were observed
[0243] ×: 10 or more peelings were observed in the vapor deposited layer
[0244] <Examples of various materials>
[0245] The following materials were used for the methacrylic copolymer (a), the styrene-maleic anhydride copolymer, the methacrylic resin and the resin composition (T) of the present invention.
[0246] Methacrylic acid copolymer (a-6): PLEXIMID TT50 manufactured by Polyplastics Evonik Corporation (Mw = 76,000, MMA / N-methylglutarimide = 30% / 70%, Tg = 151°C, saturated water absorption = 3.8%)
[0247] Methacrylic acid copolymer (a-7): PLEXIGLAS hw55Clear manufactured by Polyplastics Evonik Corporation (Mw = 141000, MMA / styrene / maleic anhydride = 74% / 15% / 9%, Tg = 121°C, saturated water absorption = 2.2%)
[0248] Styrene-maleic anhydride copolymer: XIRAN3500 manufactured by POLYSCOPE (Mw = 80,000, styrene / maleic anhydride = 74% / 26%, Tg = 160°C, saturated water absorption = 0.3%)
[0249] Methacrylic resin: Parapet HR manufactured by Kuraray Co., Ltd. (Mw = 90,000, MMA / MA = 99.3% / 0.7%, Tg = 117°C, saturated water absorption = 2.0%)
[0250] Resin composition (T-1): SD POLYCA 300 series manufactured by Sumika Polycarbonate Co., Ltd. (Mw = 50,000, Tg = 150°C, saturated water absorption = 0.3%)
[0251] Resin composition (T-2): Parapet GR-F manufactured by Kuraray Co., Ltd.
[0252] (Production Example: Precursor polymer)
[0253] The precursor polymers (p-1) to (p-5) of this production example were produced by the following method.
[0254] Precursor polymer (p-1) to (p-2)
[0255] Into an autoclave with a stirrer, 68.0 parts by mass of purified methyl methacrylate (MMA), 28.0 parts by mass of α-methylstyrene (αMSt), 7.0 parts by mass of styrene (St), 0.05 parts by mass of 2,2'-azobis(2-methylpropionitrile) (AIBN) and 0.01 parts by mass of n-octyl mercaptan (n-OM) were added and uniformly dissolved to obtain a polymerization raw material. Nitrogen was blown into the reaction raw material to remove dissolved oxygen to 3ppm. Next, the continuous flow tank reactor equipped with a brine condenser was replaced with nitrogen. The polymerization raw material was continuously supplied to the above-mentioned tank reactor at a constant flow rate with an average residence time of 3.0 hours, and bulk polymerization was carried out at a polymerization temperature of 140°C, and a liquid containing a precursor polymer was continuously discharged from the tank reactor. It should be noted that the pressure in the tank reactor was adjusted using a pressure regulating valve connected to the brine condenser. The polymerization conversion rate is the value recorded in Table 1. Next, the liquid discharged from the reactor is heated to 210°C and supplied to a twin-screw extruder controlled at 230°C. The volatile components mainly composed of unreacted monomers are separated and removed in the twin-screw extruder, and the precursor polymer is extruded in the form of strands. The strands are cut with a granulator to obtain a precursor polymer (p-1). The weight average molecular weight Mw of the obtained precursor polymer (p-1) is measured. The results are shown in Table 1. In addition, 77.5 parts by mass of purified methyl methacrylate (MMA), 17.5 parts by mass of α-methylstyrene (αMSt), 5.0 parts by mass of styrene (St), 0.04 parts by mass of 2,2'-azobis(2-methylpropionitrile) (AIBN) and 0.053 parts by mass of n-octyl mercaptan (n-OM) are used, and the average residence time is changed to 2.5 hours. In addition, the same operation as the preparation method of the above-mentioned precursor polymer (p-1) is performed to obtain a precursor polymer (p-2). Table 1 also shows the polymerization conversion rate and weight average molecular weight Mw of the precursor polymer (p-2).
[0256] Precursor polymer (p-3)
[0257] Into an autoclave with a stirrer, 60.0 parts by mass of purified methyl methacrylate (MMA), 25.0 parts by mass of α-methylstyrene (αMSt), 15.0 parts by mass of maleic anhydride (Mah), 0.005 parts by mass of 2,2'-azobis(2-methylpropionitrile) (AIBN) and 0.02 parts by mass of n-octyl mercaptan (n-OM) were added and uniformly dissolved to obtain a polymerization raw material. Nitrogen was blown into the reaction raw material to remove dissolved oxygen to 3ppm. Next, the continuous flow tank reactor equipped with a brine condenser was replaced with nitrogen. The polymerization raw material was continuously supplied to the above-mentioned tank reactor at a constant flow rate with an average residence time of 2 hours, and bulk polymerization was carried out at a polymerization temperature of 130°C, and a liquid containing a precursor polymer was continuously discharged from the tank reactor. It should be noted that the pressure in the tank reactor was adjusted using a pressure regulating valve connected to the brine condenser. The polymerization conversion rate is the value recorded in Table 1. Next, the liquid discharged from the reactor was heated to 230°C and supplied to a twin-screw extruder controlled at 240°C. The volatile components mainly composed of unreacted monomers were separated and removed in the twin-screw extruder, and the precursor polymer was extruded in the form of strands. The strands were cut with a pelletizer to obtain a precursor polymer (p-3). The weight average molecular weight Mw of the obtained precursor polymer (p-3) was measured.
[0258] Table 1 shows the results.
[0259] Precursor polymer (p-4)
[0260] 75.0 parts by mass of purified methyl methacrylate (MMA), 25.0 parts by mass of α-methylstyrene (αMSt), 0.004 parts by mass of 2,2'-azobis(2-methylpropionitrile) (AIBN) and 0.02 parts by mass of n-octyl mercaptan (n-OM) were added to an autoclave with a stirrer and uniformly dissolved to obtain a polymerization raw material. Nitrogen was blown into the reaction raw material to remove dissolved oxygen to 3 ppm. Next, the continuous flow tank reactor equipped with a brine condenser was replaced with nitrogen. The polymerization raw material was continuously supplied to the above-mentioned tank reactor at a constant flow rate with an average residence time of 3 hours, and bulk polymerization was carried out at a polymerization temperature of 130°C, and a liquid containing a precursor polymer was continuously discharged from the tank reactor. It should be noted that the pressure in the tank reactor was adjusted using a pressure regulating valve connected to the brine condenser. The polymerization conversion rate is the value recorded in Table 1. Next, the liquid discharged from the reactor was heated to 230°C and supplied to a twin-screw extruder controlled at 240°C. The volatile components mainly composed of unreacted monomers were separated and removed in the twin-screw extruder, and the precursor polymer was extruded in the form of strands. The strands were cut with a pelletizer to obtain a precursor polymer (p-4). The weight average molecular weight Mw of the obtained precursor polymer (p-4) was measured. The results are shown in Table 1.
[0261] Precursor polymer (p-5)
[0262] According to the method for producing the copolymer (A) described in the [Example] section of Japanese Patent Publication No. 2003-231785, an MS resin (a copolymer of methyl methacrylate (MMA) and styrene (St)) was polymerized. The mass ratio of MMA and St put into the autoclave was changed to obtain a precursor polymer (p-5) having a content of styrene monomer units of 20% by mass. The weight average molecular weight Mw of the obtained precursor polymer (p-5) was measured. The results are shown in Table 1.
[0263] <Production Example 1>
[0264] The precursor polymer (p-1) is supplied at 15 kg / hour to the conveying section of a twin-screw extruder (manufactured by Nippon Steel Works, Ltd.; trade name TEX30α-77AW-3V) which is composed of a conveying section, a melt-kneading section, a devolatilization section and a discharge section, and the screw speed is set to 150 rpm and the temperature is set to 210-270°C. In the melt-kneading section provided with a kneading block, the amount of monomethylamine added is adjusted in such a way that the content of the structural unit derived from glutarimide in Table 1 is obtained, and the precursor polymer (p-1) is reacted with the monomethylamine by injecting it from the additive supply port of the twin-screw extruder. It should be noted that the melt-kneading section is almost always composed of a kneading disk, and sealing elements are installed at both ends thereof. In the devolatilization section, by-products and excess monomethylamine are volatilized from the molten resin passing through the melt-kneading section and discharged through a plurality of vents.
[0265] The molten resin extruded in the form of strands from a die disposed at the end of the discharge portion of the twin-screw extruder was cooled in a water tank and then cut using a pelletizer to obtain a granular methacrylic copolymer (a-1). The content of the structural unit derived from glutarimide in the methacrylic copolymer (a-1) was 53% by weight. The composition and weight average molecular weight Mw of the methacrylic copolymer (a-1) are shown in Table 1.
[0266]
[0267] <Production Example 2>
[0268] A methacrylic acid copolymer (a-2) was obtained by the same method as in Example 1 except that the amount of monomethylamine added was changed so that the content of the structural unit derived from glutarimide was 70 wt %. Table 1 shows the composition and weight average molecular weight Mw of the methacrylic acid copolymer (a-2).
[0269] <Production Example 3>
[0270] A methacrylic acid copolymer (a-3) was obtained by the same method as in Example 1 except that the precursor polymer (p-2) was used and the amount of monomethylamine added was changed so that the content of the structural unit derived from glutarimide was 38% by weight. The composition and weight average molecular weight Mw of the methacrylic acid copolymer (a-3) are shown in Table 1.
[0271] <Production Example 4>
[0272] A methacrylic acid copolymer (a-4) was obtained by the same method as in Example 1 except that the precursor polymer (p-3) was used and the amount of monomethylamine added was changed so that the content of the structural unit derived from glutarimide was 25% by weight and the content of the structural unit derived from maleimide was 15% by weight. The composition and weight average molecular weight Mw of the methacrylic acid copolymer (a-4) are shown in Table 1.
[0273] <Production Example 5>
[0274] A methacrylic acid copolymer (a-5) was obtained by the same method as in Example 1 except that the precursor polymer (p-2) was used and the amount of monomethylamine added was changed so that the content of the structural unit derived from glutarimide was 15% by weight. The composition and weight average molecular weight Mw of the methacrylic acid copolymer (a-5) are shown in Table 1.
[0275] <Production Example 6>
[0276] A methacrylic acid copolymer (a-8) was obtained by the same method as in Example 1 except that the precursor polymer (p-4) was used and the amount of monomethylamine added was changed so that the content of the structural unit derived from glutarimide was 30% by weight. The composition and weight average molecular weight Mw of the methacrylic acid copolymer (a-8) are shown in Table 1.
[0277] <Production Example 7>
[0278] A methacrylic acid copolymer (a-9) was obtained by the same method as in Example 1 except that the precursor polymer (p-5) was used and the amount of monomethylamine added was changed so that the content of the structural unit derived from glutarimide was 48% by weight. The composition and weight average molecular weight Mw of the methacrylic acid copolymer (a-9) are shown in Table 1.
[0279] <Production Example 8>
[0280] The methacrylic copolymer (a-1) was melt-kneaded and extruded at 250° C. using a twin-screw extruder having a shaft diameter of 20 mm to obtain a methacrylic resin composition (I-1).
[0281] <Production Examples 9 to 19>
[0282] Methacrylic resin compositions (I-2) to (I-12) were obtained by the same method as in Production Example 6 except for the formulations described in Table 2. Table 2 shows the evaluation results.
[0283]
[0284] <Example 1>
[0285] The two resins, a layer resin formed by the resin composition (T) and a layer resin formed by the methacrylic resin composition (I), were respectively put into the hoppers of different 25mmφ vent-type single-screw extruders (manufactured by GMENGINEER JNG; VGM25-28EX) for melt mixing, and then these resin compositions were introduced into the connecting block and co-extruded at an extrusion temperature of 250°C using a multi-manifold die. The thickness of each layer is adjusted by adjusting the discharge amount of each resin composition. Next, the co-extruded resin composition in a molten state is sandwiched between the first cooling roller and the second cooling roller adjacent to each other, wound on the second cooling roller, sandwiched between the second cooling roller and the third cooling roller, and wound on the third cooling roller, thereby cooling. The thermoplastic resin layer obtained after cooling is pulled by a pair of pulling rollers. It should be noted that the layer formed by the methacrylic resin composition (I) is brought into contact with the third cooling roller. In this way, a two-layer structure of a laminated substrate film for vapor deposition is manufactured. The evaluation results of the laminated substrate film for vapor deposition are shown in Table 3.
[0286] <Examples 2 to 6, Comparative Examples 1 to 7>
[0287] The deposition laminated substrate films described in Examples 2 to 6 and Comparative Examples 1 to 7 were produced in the same manner as in Example 1 except that the resin composition (T) and the methacrylic resin composition (I) described in Table 3 were used. The evaluation results of the deposition laminated substrate films are shown in Table 3.
[0288]
[0289] As shown in Table 3, the laminated films obtained in Examples 1 to 6 have excellent appearance quality, dimensional stability, and flexibility by using methacrylic resin compositions (I-1) to (I-5) having high total light transmittance and Charpy impact strength, excellent fluidity, and heat-resistant and low water absorption. In addition, the resin composition has high wetting tension, so the laminated film of the present invention has excellent adhesion to the vapor deposition layer. From the above, it can be seen that the laminated films of Examples 1 to 6 are suitable as vapor deposition substrates.
[0290] In contrast, for laminated films (Comparative Examples 1, 3, 4, and 7) using methacrylic resin compositions (I-6), (I-8), (I-9), and (I-12) having insufficient heat resistance and low water absorption, dimensional stability deteriorates. In addition, for laminated films (Comparative Examples 2, 3, and 6) using methacrylic resin compositions (I-7), (I-8), and (I-11) having low total light transmittance, fluidity, and heat decomposition resistance, poor appearance is likely to occur. In addition, for laminated films (Comparative Example 1) using methacrylic resin composition (I-6) having low wetting tension and laminated bodies (Comparative Example 5) using resin composition (I-10) having low Charpy impact strength, adhesion to the vapor-deposited layer and flexibility are reduced.
Claims
1. A laminated substrate film for vapor deposition, comprising a layer formed of a methacrylic resin composition (I) containing a methacrylic copolymer (a) and having a glass transition temperature of 135° C. or higher, and a layer formed of a resin composition (T) containing a thermoplastic resin (b), The methacrylic copolymer (a) comprises 5 to 73% by mass of methyl methacrylate units, 25 to 70% by mass of a structural unit (r) represented by the following formula (1), 1 to 48% by mass of an α-methylstyrene unit, 1 to 48% by mass of at least one selected from the group consisting of a styrene unit and a maleic anhydride unit, and 0 to 20% by mass of an unsubstituted or N-substituted maleimide unit. In formula (I), R 1 are each independently a hydrogen atom or a methyl group, R 2 It is a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an organic group having 6 to 15 carbon atoms including an aromatic ring.
2. The laminated substrate film for vapor deposition according to claim 1, wherein The glass transition temperature of the methacrylic resin composition (I) is 145° C. or higher.
3. The laminated substrate film for vapor deposition according to claim 1, wherein The saturated water absorption of the methacrylic resin composition (I) is 3.0% by mass or less.
4. The laminated substrate film for vapor deposition according to claim 1, wherein The thermoplastic resin (b) is a polycarbonate resin.
5. The laminated substrate film for vapor deposition according to claim 1, wherein The layer formed of the methacrylic resin composition (I) and the layer formed of the resin composition (T) are co-extruded molded products.
6. The laminated substrate film for vapor deposition according to claim 1, wherein An anchor layer is laminated on the layer formed of the methacrylic resin composition (I).
7. A vapor-deposited laminated film, characterized in that: In the laminated base film for vapor deposition according to claim 1, a layer formed by a methacrylic resin composition (I) is laminated on one surface of a layer formed by a resin composition (T), and a vapor deposition layer is provided on the surface on the side of the layer formed by the methacrylic resin composition (I).
8. A vapor-deposited laminated film, characterized in that: In the laminated base film for vapor deposition according to claim 1, in which layers composed of the methacrylic resin composition (I) are laminated on both surfaces of a layer composed of the resin composition (T), a vapor deposition layer is provided on either surface.
9. A sheet with a metallic texture, characterized in that: A thermoplastic resin sheet is laminated on the vapor-deposited layer side of the vapor-deposited laminate film according to claim 7 or 8.
10. The metallic sheet according to claim 9, wherein: The vapor-deposited layer and the thermoplastic resin sheet are laminated with the adhesive layer interposed therebetween.
11. The metallic sheet according to claim 9, wherein: The vapor deposited layer and the thermoplastic resin sheet are laminated by dry lamination.
12. A metallic texture formed product, characterized in that: The vapor-deposited layer side surface of the vapor-deposited laminated film according to claim 7 or claim 8 is bonded to a molded article.
13. A metallic texture formed product, characterized in that: The metallic sheet according to claim 9 is formed by laminating the surface of the metallic sheet on which the thermoplastic resin sheet is laminated to a molded article.
14. A metallic texture formed product, characterized in that: The surface of the metallic sheet according to claim 10 on which the thermoplastic resin sheet is laminated is bonded to a molded article.
15. A metallic texture formed product, characterized in that: The surface of the metallic sheet according to claim 11 on which the thermoplastic resin sheet is laminated is bonded to a molded article.
Citation Information
Patent Citations
Continuous modification of resin
JP1986026924B2
Method for producing imidized copolymers
JP1995042332B2
Method for imidating styrene / maleic anhydride polymer
JP1997100322A
Production and use of clear heat-resistant resin
JP2000230016A
Method of manufacturing for transparent heat resistant resin and use of the same
JP2001151814A